Pengenalan Kitab – Kitab Hadits Dan Metode Penyusunan - Muhammad Baihaqi; Zikri Darussamin (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Hadith books occupy a crucial position in the treasury of Islamic scholarship as the primary source after the Qur'an. Therefore, their existence requires a thorough understanding of the compilation methods and characteristics of each book. The diverse forms and systematics of compilation of hadith books, such as al-Jami', al-Sunan, al-Musnad, al-Muwatta', and al-Mustadrak, demonstrate the methodological developments of scholars in preserving, codifying, and facilitating access to the life of the Prophet Muhammad ﷺ. This article aims to explain the meaning and scope of hadith books, introduce various compilation methods, and describe the most renowned hadith books in the Islamic tradition. This research employs library research through analysis of various classical works and relevant contemporary scholarly literature. The results show that each type of book has its own orientation and method, ranging from thematic approaches, fiqh (jurisprudence), sanad (chain of narrators), to additional verification of previous works. Famous books such as Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Musnad Ahmad, Sunan Abī Dāwūd, and al-Mustadrak testify to the scholars' meticulousness in preserving the authenticity of the Sunnah. These varied methods reflect the scientific and historical needs of the Muslim community, but ultimately lead to the same primary goal: preserving and maintaining the purity of the hadith of the Prophet ﷺ.